El derecho constitucional a recurrir y la pertinencia de la limitación de impugnación en el régimen societario de la Compañía Anónima. - Ruiz Valdiviezo, Jhoan Alejandro (2023)
The Ecuadorian legal framework is characterized by being a guarantee within the application of various fundamental rights. These rights cannot be excluded from any type of judicial process, since they are recognized by the Constitution of the Republic, these are of a higher hierarchy, and therefore, they cannot be restricted or declared inapplicable by a lesser norm. legal status or hegemony. The objective of this titling work is to determine through a doctrinal legal study the relevance of limiting the right of challenge in the corporate legislation that regulates the anonymous company to establish its scope. The study design was non-experimental, since the analysis units were analyzed to determine a relationship of variables, and they were not modified. It was concluded that the regulation of the challenge in Ecuadorian corporate law is limited by some legal flaws, which jeopardize its proper exercise and consequently the rights of partners. The problem in question becomes evident because the precepts of articles 215 and 249 of the Companies Law contain limitations on the right to challenge, stating that for its exercise the existence of a number of partners that represent at least the twenty-five percent of the share capital, so if this percentage is not reached, the affected partners are left without the possibility of exercising their right to challenge.